Angiotensin-Converting Enzyme Inhibitory and Antioxidant Activities of Kam-Lung-Rad-Cha-Si, A Thai Herbal Formulation, Extracts - Chaiyawatthanananthn, Pannawat; Houngiam, Katanchalee; Prajuabjinda, Onmanee; Itharat, Arunporn (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Hypertension is induced by angiotensin-converting enzyme (ACE) and oxidant activities. A Thai traditional medicinal, Kam-Lung-Rad-Cha-Si, recipe (KLR) is used for treating hypertension. Moreover, there is no scientific report supporting the use of the KLR in the Thai traditional theory. Objectives: To investigate the effects of the aqueous and ethanolic KLR extracts on ACE inhibitory and antioxidant activities. Methods: Thirty-four medicinal plants were extracted with 95% ethanol maceration (KLRE) and aqueous decoction (KLRA). All extracts were measured total phenolic contents (TPC) and total flavonoid contents (TFC). The extracts were evaluated for antioxidant activity with DPPH radicalscavenging assay and anti-hypertensive effect byACE inhibitory assay by comparing with positive controls i.e., butylated hydroxytoluene (BHT) and Captopril, respectively. Results: Our results showed that KLRA and KLRE had TPC (192.36 ± 1.71 and 92.24 ± 1.83 mg GAE/g, respectively) and TFC (138.18 ± 1.14 and 85.88 ± 1.67 mg QE/g, respectively). The results indicated that KLRA and KLRE had an antioxidant capacity. Moreover, KLRA and KLRE presented an antioxidant activity by EC50 values were 12.45 ± 0.47 and 17.26 ± 0.80 µg/mL, respectively, and KLRAdid not differ to inhibit DPPH radicals when compared with BHT (10.94 ± 0.24 µg/mL). In addition, KLRA and KLRE inhibited the ACE activity and had betterACE inhibition than Captopril by IC50 values were 36.57 ± 1.13, 30.75 ± 1.04, and 8.41 ± 0.85 µg/mL, respectively. Conclusions: The KLRA and the KLRE presented antioxidant and anti-hypertensive effects. Thus, the KLR remedy may be used to treat hypertension following the Thai traditional medicine theory.